Gal-1 (Galectin-1) Upregulation Contributes to Abdominal Aortic Aneurysm Progression by Enhancing Vascular Inflammation - Chiang, Ming-Tsai; Chen, I-Ming; Hsu, Fu-Fei; Chen, Yen-Hui; Tsai, Min-Shao; Hsu, Yaw-Wen; Leu, Hsin-Bang; Huang, Po-Hsun; Chen, Jaw-Wen; Liu, Fu-Tong; Chen, Ying-Hwa; Chau, Lee-Young (Arteriosclerosis, thrombosis, and vascular biology, 2021)
OBJECTIVE:Abdominal aortic aneurysm (AAA) is a vascular degenerative disease causing sudden rupture of aorta and significant mortality in elders. Nevertheless, no prognostic and therapeutic target is available for disease management. Gal-1 (galectin-1) is a β-galactoside–binding lectin constitutively expressed in vasculature with roles in maintaining vascular homeostasis. This study aims to investigate the potential involvement of Gal-1 in AAA progression. APPROACH AND RESULTS:Gal-1 was significantly elevated in circulation and aortic tissues of Ang II (angiotensin II)–infused apoE-deficient mice developing AAA. Gal-1 deficiency reduced incidence and severity of AAA with lower expression of aortic MMPs (matrix metalloproteases) and proinflammatory cytokines. TNFα (tumor necrosis factor alpha) induced Gal-1 expression in cultured vascular smooth muscle cells and adventitial fibroblasts. Gal-1 deletion enhanced TNFα-induced MMP9 expression in fibroblasts but not vascular smooth muscle cells. Cysteinyl-labeling assay demonstrated that aortic Gal-1 exhibited susceptibility to oxidation in vivo. Recombinant oxidized Gal-1 induced expression of MMP9 and inflammatory cytokines to various extents in macrophages, vascular smooth muscle cells, and fibroblasts through activation of MAP kinase signaling. Clinically, serum MMP9 level was significantly higher in both patients with AAA and coronary artery disease than in control subjects, whereas serum Gal-1 level was elevated in patients with AAA but not coronary artery disease when compared with controls. CONCLUSIONS:Gal-1 is highly induced and contributes to AAA by enhancing matrix degradation activity and inflammatory responses in experimental model. The pathological link between Gal-1 and AAA is also observed in human patients. These findings support the potential of Gal-1 as a disease biomarker and therapeutic target of AAA.